2015
DOI: 10.4314/ijbcs.v9i4.8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation de l’infestation des Loranthaceae sur les ligneux des agroécosystèmes de la région du Sud-Comoé (Côte d’Ivoire)

Abstract: RESUME Evaluation of the infestation of wood Loranthaceae on agroecosystems of the Sud-Comoé region (Côte d'Ivoire) ABSTRACTIn Côte d'Ivoire, parasites vascular plants of the family Loranthaceae are a major threat to many species and wild fruit given the extent of the damage. The present study was undertaken with the aim to contributing to better understanding Loranthaceae and parasitism on the woody flora of agroecosystems (cocoa, coffee) in the Sud-Comoé (Côte d'Ivoire). In orchards, Loranthaceae species fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
1
5
0
2
Order By: Relevance
“…Calotropis procera was found among the least sensitive host species in Benin (Houenon et al, 2012) and Mangifera indica was said to be resistant to parasitic plants (Dibong et al, 2008). These results corroborate those of Dibong et al (2008) which presented Mangifera indica as a resistant species to the parasitism of Loranthaceae and differ from those of Feguem (2011) and Amon et al (2015). These authors showed that Mangifera indica was parasitized in the North-West region of Cameroon and South-Comoé region of Ivory-Coast respectively.…”
Section: Loranthaceae Host Species and Parasitismsupporting
confidence: 90%
“…Calotropis procera was found among the least sensitive host species in Benin (Houenon et al, 2012) and Mangifera indica was said to be resistant to parasitic plants (Dibong et al, 2008). These results corroborate those of Dibong et al (2008) which presented Mangifera indica as a resistant species to the parasitism of Loranthaceae and differ from those of Feguem (2011) and Amon et al (2015). These authors showed that Mangifera indica was parasitized in the North-West region of Cameroon and South-Comoé region of Ivory-Coast respectively.…”
Section: Loranthaceae Host Species and Parasitismsupporting
confidence: 90%
“…Elle se présente comme l'association de forêts claires et de savanes (Amon et al, 2015) se développant sur des sols ferralitiques moyennement désaturés et moins développés. Ces sols présentent des phénomènes d'induration faibles et irréguliers.…”
Section: Materiel Et Methodes Site D'étudeunclassified
“…The study on trees and shrubs host to epiphytoid parasites (Loranthaceae) in cocoa tree based agrosystems in Daloa department have allowed to inventory 73 host species of Loranthaceae belonging to 55 genera to 22 families. This taxonomic diversity of 55 genera and 73 species is significantly lower than that of the 77 genera and 116 species obtained in agrosystems in the South-east of Côte d'Ivoire (Amon, 2014) [3] and that of 81 genera and 99 species registered by Soro (2010) [22] in Oumé, Gagnoa and Soubré, in the Central-West and in the South-West of the country. On the other hand, it is clearly higher than the 34 genera and 41 species recorded in the agrosystems of the riparian areas of the University of Lorougnon Guédé, in the Central-West of Côte d'Ivoire (Sako, 2019) [18 ].…”
Section: Discussionmentioning
confidence: 62%